2009
DOI: 10.3390/ijerph6112898
|View full text |Cite
|
Sign up to set email alerts
|

Examining Factors in the Research Institute on Addictions Self-Inventory (RIASI): Associations with Alcohol Use and Problems at Assessment and Follow-Up

Abstract: Impaired driving is a leading cause of alcohol-related deaths and injuries. Rehabilitation or remedial programs, involving assessment and screening of convicted impaired drivers to determine problem severity and appropriate programs, are an important component of society’s response to this problem. Ontario’s remedial program, Back on Track (BOT), involves an assessment process that includes administration of the Research Institute on Addictions Self-Inventory (RIASI) to determine assignment to an education or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The RIASI generates two scores, a total score (RIASI-T) based on the full instrument, and the recidivism score (RIASI-R). Eight factors have been identified within the RIASI, reflecting problem areas associated with alcohol use (Mann et al 2009). In addition, several other measures are collected at assessment, including the Adverse Consequences of Substance Use Scale (ACSUS; Mann et al 2006), measures of substance use in the previous 90 days, contacts with health (including addictions-related) and corrections services in the previous 90 days, and various demographic measures (e.g., age, gender).…”
Section: Registration Assessment and Follow-up Measuresmentioning
confidence: 99%
“…The RIASI generates two scores, a total score (RIASI-T) based on the full instrument, and the recidivism score (RIASI-R). Eight factors have been identified within the RIASI, reflecting problem areas associated with alcohol use (Mann et al 2009). In addition, several other measures are collected at assessment, including the Adverse Consequences of Substance Use Scale (ACSUS; Mann et al 2006), measures of substance use in the previous 90 days, contacts with health (including addictions-related) and corrections services in the previous 90 days, and various demographic measures (e.g., age, gender).…”
Section: Registration Assessment and Follow-up Measuresmentioning
confidence: 99%
“…No one approach to screening or triaging first DUI offenders can be recommended to guide a specific policy, although Dugosh et al () identified several addiction items and primarily criminal justice factors that could be predictive of need for treatment to reduce recidivism. Other research (Mann et al., ; Shuggi, Mann, Zalcman, Chipperfield, and Nochajski, ; Wanberg et al., ) has shown that screening approaches such as the Research Institute on Addiction Screening Instrument have the potential to guide the triaging of DUI offenders. Despite this research, no screening or triaging protocol is currently available or suitable (in terms of predictive validity and alignment with state‐level laws and regulations) for use in most jurisdictions.…”
Section: Specific Deterrence Policiesmentioning
confidence: 99%
“…The assessment includes the Research Institute on Addictions Self-inventory (RIASI; Mann et al, 2009;Nochajski et al, 1995), an addictions screening instrument that was designed specifically for use with convicted drinking drivers. The RIASI is a 52-item instrument that measures distal (hostility/aggression, sensation seeking, depression, anxiety, interpersonal competence, childhood risk factors, social problems such as criminal history, health issues) and proximal factors (current drinking habits, pre-occupation with alcohol, alcohol beliefs, use of alcohol to alleviate problems, and family history) associated with alcohol or drug problems.…”
Section: Design and Settingmentioning
confidence: 99%